Overall performance measurement for logistics operations - Jamaludin, Khairur Rijal; Abdul Talib, Hayati @ Habibah; Tan, Chiaw Hooi (Universiti Teknologi Malaysia, 2006)
Logistics and Supply Chain Management (LSCM) has become common practice across all industries, however, the topic of Logistics Performance Measurement (LPM) does not receive adequate attention therein. Current logistics operations performance measurement systems in MOX (subject for the case study) are also inadequate because they rely heavily on the use of cost as a primary (if not sole) measure. More often than not, they are inconsistent with the strategic goals of the organizations, and do not consider the effects of uncertainty. In the transportation and distribution sector, as in many others, it is important to have a good performance in operations. A good performance measurement system is a necessity for a company to grow and sustain industry leadership. As an indispensable management tool, performance measurement provides the necessary assistance for performance improvement in pursuit of supply chain excellence. The main objective of this project is to study and understands the existing logistics operations performance measurement systems in MOX and identifies its drawbacks, and suggests improvements in line with the excellent practices. The scope of discussion is focusing on safety, productivity, costs and delivery reliability of the department. Interviews and discussions with management team have been conducted; strategies tools such as SWOT analysis, CPM analsyis and etc. have also been applied in executing this project. Upon completion, a set of Critical Success Factors (CSF) and Key Operational Factors (KOF) of the department will be identified and put together as an overall performance measurement matrixs for the department. As stated earlier, a good performance measurement systems supports sound management decisions. It is believed that the newly developed Overall Performance Measurement System is effective as it provides high quality, reliable, and timely information to influence management's decisions and employee's behavior.